Determinan Keramas Dengan Penyakit Kutuan Terhadap Berat Badan Pada Anak di Desa Pematang Biara - Nurly Fadila; Siti Khadijah; Angga Dwi Prasetyo; Mutiara Ashifa; Fatma Salsabila; Daffa Dhiba Oesrani; Keysha Febri Dhanty; Ghizka Aulia Putri (PT. Alahyan Publisher Sukabumi, 2024)
Pediculosis capitis is a common disease in Indonesia. The study aims to identify the shaming determinan with the incidence of pedicuinfirmcapitis in the village of gourd bay district monastery district, the serdang deli district. The study was carried out from December 16 to 17, 2023. Studies using primary data analysed by handing out questionnaires of 229 children. Data collection USES an interview sampling technique and USES a questionnaire consisting of questions about identity, body weight, how to get the disease in any way or treatment for the disease. The analysis of the data on this study is done using a descriptive method. The study was a quantitative study with a conceptual analysis that used a c-square test. As many as 125 respondents had suffered from backups and 70 of those who had hair lice affected their friends. In this study, shampooing becomes the reason children are subjected to kuples by the number of one week at 41 reponden 1x a week, 103 respondents at 2x-3x a week, 81 responders >3x a week, and 4 respondents daily shampooing. Next to those who did not treat me as many as 107 respondents while 56 reponden treated me with a comb of ticks, 42 reponden with peditox, 4 of those with hair cuts, 1 of olive oil, 2 of those with just shampooing, and 17 of those with magic chalk. It can then be deduced from study that the factors that caused the respondents to become Pediculosis capitis were those that resulted from irregular shampooing, the transmission of the family, and the transmission of a friend.